Collusion sustainability with optimal punishments and detection lags, with an application to a Cournot game - Ciarreta, Aitor; Gutiérrez-Hita, Carlos (Estudios de Economía, 2013)
In this paper we characterize optimal punishments with detection lags when the market consists of n oligopolistic firms that compete à la Cournot. It is shown how in the presence of detection lags optimal punishments fail to restore cooperation as long as the number of lags increases. Moreover, collusion sustainability is difficult to achieve also if the number of firms is low.